Investigation of the effect of COVID-19 pandemic on employees' psychological symptoms and nutritional habits - Kanbur, Savas (Progress in Nutrition, 2021)
Background: It is anticipated that the fear caused by the possible consequences of Covid-19 virus transmission and the sense of restraint caused by control applications such as quarantine may affect individuals', especially employees' psychological parameters and change their habits. Objectives: The aim of this study is explaining the effect of pandemic conditions and precautionary practices on the psychological parameters and nutritional habits of employees. Methods: In this direction, The SCL-90-R test, which was applied to 400 office workers before the pandemic, was reapplied during the pandemic period and the differences between the psychological symptoms were evaluated statistically. In addition, a mini questionnaire was applied on the change of daily nutritional habits after the pandemic. Results: In the period of pandemic compared to before the pandemic; a definite statistical difference was determined in somatization, interpersonal sensitivity, depression, anxiety, phobic anxiety, paranoid, and general symptom index symptoms. In addition, an acceptable difference was found for the increase in symptoms of paranoid ideation and obsessive-compulsive, and there was no statistical difference only in symptoms of hostility and psychoticism. In addition, it was found that the majority of the participants experienced a change in their daily eating methods. Conclusion: The increase in almost all of the psychological parameters is not evidence of psychological diseases. However, according to the average results, the parameters closest to evaluation as a problem comply with the observed behaviors in pandemic conditions. The change in nutrition methods is also thought to be a reflection of the psychological factors that changed during the pandemic period.